PENERAPAN MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN ENTREPRENEURIAL MINDSET SISWA DI SMK DARUL ULUM AS SURUR KELAS X - Hadi, Syukron; Prasetiyorini, Pudhak; Gerhani, Febrina (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Strengthening the entrepreneurial mindset at the Vocational High School (SMK) level is a strategic urgency in preparing adaptive, creative, and independent graduates amidst the dynamics of the world of work and entrepreneurship. One of the relevant learning approaches to develop students' entrepreneurial mindset is the Student Teams Achievement Division (STAD) cooperative learning model, because it is able to stimulate cooperation, communication, and individual responsibility in groups. This study aims to analyze the application of the STAD model in improving the entrepreneurial mindset of class X students at SMK Darul Ulum AS Surur, identify changes in student attitudes in the aspects of creativity, innovation, and independence, and evaluate the effectiveness of the model in improving students' cooperation and communication skills in the context of entrepreneurship. This study uses a quantitative method with a quasi-experimental approach. The research subjects were 30 class X students selected through purposive sampling techniques. The data collection instrument used was a validated entrepreneurial mindset questionnaire supported by documentation and observation. The results of the study showed that the application of the STAD cooperative learning model had a significant effect on improving students' entrepreneurial mindset. Based on the results of the paired sample t-test, a significance value of 0.001 <0.05 was obtained, so H0 was rejected and H1 was accepted. This means that there is a significant difference between the pre-test and post-test results of students' entrepreneurial mindset after the STAD type cooperative learning model was applied.